2020
DOI: 10.1097/md.0000000000019303
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the association between psoriasis and hypertension with adjustment for covariates

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
3
19
1
2
Order By: Relevance
“… 28 A cohort study from the University of Toronto also showed a higher prevalence of HTN in PsA compared with patients with psoriasis only (OR 2.17, 95% CI 1.22–3.83) after adjusting for several demographic factors, psoriasis-related factors, medications, and comorbidities. 6 In a meta-analysis by Duan et al ., 29 the odds of HTN was higher than the general population only in severe psoriasis (OR 1.13, 95% CI 1.03–1.25), and not in mild psoriasis (OR 1.09, 95% CI 0.98–1.22). Therefore, an association with increased systemic inflammation is likely; and PsA is thought to be at the severe end of the psoriatic disease spectrum in general.…”
Section: Metabolic Disease In Psamentioning
confidence: 74%
“… 28 A cohort study from the University of Toronto also showed a higher prevalence of HTN in PsA compared with patients with psoriasis only (OR 2.17, 95% CI 1.22–3.83) after adjusting for several demographic factors, psoriasis-related factors, medications, and comorbidities. 6 In a meta-analysis by Duan et al ., 29 the odds of HTN was higher than the general population only in severe psoriasis (OR 1.13, 95% CI 1.03–1.25), and not in mild psoriasis (OR 1.09, 95% CI 0.98–1.22). Therefore, an association with increased systemic inflammation is likely; and PsA is thought to be at the severe end of the psoriatic disease spectrum in general.…”
Section: Metabolic Disease In Psamentioning
confidence: 74%
“…1 It presents with well-defined, red, scaly plaques that can be pruritic or painful and is associated with comorbidities including psoriatic arthritis, hypertension, obesity and diabetes. [2][3][4][5][6][7] Psoriatic inflammation is primarily T-helper (Th)17 and Th1-driven, and is mediated by cytokines such as tumour necrosis factor (TNF)-α, interleukin (IL)-17 and IL-23. [8][9][10][11] Systemic treatment options for severe psoriasis include broadly-acting oral immunomodulators, such as methotrexate and ciclosporin, and biologics, which are monoclonal immunoglobulin-G (IgG) molecules (with the exception of etanercept) targeting specific cytokines or receptors involved in psoriasis pathogenesis (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Data from epidemiologic studies show that hypertension is more prevalent among psoriasis patients, and prevalence is associated with psoriasis severity [ 19 , 26 28 ]. A recently published meta-analysis demonstrates that psoriasis is associated with an increased risk of hypertension compared with those without psoriasis [ 29 ].…”
Section: Association Between Psoriasis and Cardiovascular Risk Factormentioning
confidence: 99%